Reclassification of the downtown area of São Paulo - Alves, Glória da Anunciação (Estudos Avançados, 2011)
Since the late 80's of the 20th century, downtown São Paulo has been through a process of spacial transformation which is intended to reclassify and endow it with elements of modernization in order to keep it in the network of world cities, i.e., spaces that control and command the process of capitalist reproduction. However, these transformations imply changes in the lives of the population living in that area. The strategies of the actors (primarily state and private) involved in urban renewal tend to reinforce social and spatial differentiation, with an attempt to change the population profile, which can follow the world trend of gentrification of central areas.